A highly sensitive semi-nested real-time PCR utilizing oligospermine-conjugated degenerate primers for the detection of diverse strains of small ruminant lentiviruses. (June 2020) - Chassalevris, Taxiarchis; Chaintoutis, Serafeim C.; Apostolidi, Evangelia D.; Giadinis, Nektarios D.; Vlemmas, Ioannis; Brellou, Georgia D.; Dovas, Chrysostomos I.
Abstract: Small ruminant lentiviruses (SRLVs) are highly diverse retroviruses infecting sheep and goats. Although PCR-based testing is being utilized for diagnostics, its application is hampered by various factors. These include, among others, the exceptionally high genetic variability of SRLVs, as well as the low number of infected blood monocytes. For this reason, a highly sensitive and specific semi-nested real-time PCR for proviral DNA detection and quantification was developed. The method is innovative in that a) its design is based on selecting the preferred codon usage in the targeted conserved genomic regions and b) oligospermine-conjugated degenerate primers with increased Tm were utilized. Modifications permitted primer/template duplex formation in the cases of mismatches due to sporadic nucleotide polymorphisms in a number of variant SRLV strains and consequently, the detection of highly diverse SRLV strains. The potential loss of analytical sensitivity and specificity was counterbalanced by including a semi-nested step in combination with LNA probes. An in silico procedure for the evaluation of hybridization efficiency of the designed oligonucleotides to all known targeted variants was also implemented. The method presents a linear range of quantification over a 3-log10 range and a limit of detection of 3.9 proviral dsDNA copies per reaction. Its diagnostic performance was evaluated by testing field samples from seropositive and seronegative animals, followed by phylogenetic analysis of the strains detected. To further increase the diagnostic sensitivity, a DNA extraction protocol for blood leukocytes was developed and evaluated. A minimum of 500 ng input DNA is recommended for PCR-based detection of SRLV proviral DNA, given the low numbers of infected blood monocytes. The developed methodology may serve as a useful tool, which can be adjusted for the quantitative detection of viruses exhibiting high genetic variability. Highlights: A highly sensitive and specific semi-nested real-time PCR for proviral DNA detection and quantification was developed. Hybridization efficiency of the designed oligonucleotides to all known targeted variants was also estimated in silico . To increase the diagnostic sensitivity a DNA extraction protocol for blood leukocytes was developed. The methodology for degenerate primer design can be adjusted for the detection of viruses with high genetic variability.